Firearm suicide in New York City in the 1990s - Piper, T M (BMJ Group, 2006)
OBJECTIVE: Across the US, firearms are used in approximately 60% of all suicide deaths. Little research has assessed the role and determinants of firearms in suicide in major urban areas. METHODS: The authors collected data on all suicide deaths between 1990 and 2000 from the Office of the Chief Medical Examiner of New York City (NYC) and assessed trends and correlates of firearm related suicide deaths. RESULTS: During the period studied, there were a total of 6008 suicides in NYC; 1200 (20.0%) were firearm related suicides. There was a decrease in total suicides, total firearm suicides, and the proportion of firearm related suicides. In multivariable modeling, characteristics of suicide decedents associated with a greater likelihood of firearm suicide were: male, black race, residing in the outer boroughs, and use of cannabis. CONCLUSIONS: The proportion of suicides caused by firearms in NYC is low compared to other parts of the US; differential access to means of committing suicide and the differential importance of firearms in different racial and ethnic groups may contribute to this observation. Innovative, local population based interventions that target non‐firearm related suicide may contribute to lower suicide mortality overall in urban areas.